Understanding untreated hypertension from patients' point of view: A qualitative study in rural Yogyakarta province, Indonesia. (September 2018) - Rahmawati, Riana; Bajorek, Beata
Objectives: This study aimed to explore perspectives about hypertension from patients who do not take anti-hypertensive medications. Factors that shape their perspectives as well as patients' expectations were also canvassed. Method: Individual, face-to-face interviews were conducted with 30 people (≥45 years old) living in rural villages, diagnosed with hypertension, who had not taken any anti-hypertensive medications for at least one year. Interviews were audiotaped, transcribed verbatim and thematically analysed. Results: Four themes emerged: (1) alternative medicines for managing high blood pressure; (2) accessing health care services; (3) the need for anti-hypertensive medications; and (4) existing support and patients' expectations. Reluctance to take anti-hypertensive medications was influenced by patients' beliefs in personal health threats and the effectiveness of anti-hypertensive medications, high self-efficacy for taking alternative medicines, the lack of recommendation regarding hypertension treatment, and barriers to accessing supplies of medicines. Conclusion: Despite their awareness of being diagnosed with hypertension, patients undervalued visiting a health professional to control their high blood pressure. Health strategies need to consider patients' beliefs, concerns and expectations. Providing an accessible, affordable and adequate supply of hypertension medication is also key to any programs designed to optimise hypertension management.